Pengaruh Live Streaming, Harga dan Personal Branding terhadap Keputusan Pembelian Konsumen Pengguna Aplikasi Tiktok - Pranadewi, Anissa; Hildayanti, Siti Komariah; Emilda, Emilda (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
TikTok has become the most popular as a social media platform for making purchases. Tiktok is a very creative e-commerce feature to connect sellers, buyers and content creators to provide an exciting experience through live streaming. This type of research is quantitative descriptive. Data sources come from primary data and secondary data by distributing questionnaires. A total of 384 respondents were collected through distributing questionnaires to consumers using the Tiktok application in Palembang City, where the population is unknown using the Lemeshow formula. The sampling technique used was purposive sampling. The analytical method used is descriptive analysis and multiple regression analysis using SPSS Version 27. The analysis used is a quantitative technique from the results of distributing questionnaires. The results of this research show that partially the variables live streaming, price and personal branding each have a positive and significant effect on purchasing decisions (prob < 0.000 < alpha = 0.05). Simultaneously, the variables live streaming, price and personal branding have a positive and significant effect on increasing purchasing decisions (prob < 0.000 < alpha = 0.05).Based on the results of correlation testing, live streaming, price and personal branding have a very strong and positive correlation with purchasing decisions. By determining live streaming, price and personal branding influence purchasing decisions by 64.3% and the remaining 35.7% of the influence on purchasing decisions is influenced by other variables outside of this research.